Association Mapping Identifies Markers Linked with Yield Traits in an Oil Palm Breeding Population - Chuenpom, Nipha; Volkaert, Hugo (Thai Journal of Science and Technology, 2017)
Abstract Oil palm (Elaeis guineensis) is an important oil crop for human consumption worldwide. Oil production is an interested trait to get more value of palm oil. Oil yield traits in an oil palm breeding program is difficult as oil palm is a highly heterozygous out-crossing crop with a long life cycle and large size. This research aims to identify Single Nucleotide Polymorphism (SNP) markers linked with oil palm yield traits. Total 40 candidate SNP markers were tested with 499 individual palms from an unrelated set of 32 families using association testing for quantitative traits. 9 SSR markers were used to estimate population structure and kinship relationships. The results indicated that the genotypes at 36 markers associated with oil yield traits (BN, ABW, FFB and PH combined) at significant statistical P-value, corrected for multiple testing. Eg_Pairs05 and SSCP0020 were highly significant associated with traits that might be high potential markers for oil palm breeding in the future. Keywords: GWAS; SNP marker; marker assisted selection (MAS)